Perancangan Sistem Notifikasi Serta Kendali Suhu dan Kelembapan Menggunakan Aplikasi BLYNK Untuk Budidaya Jamur Tiram - Akalily Mardhiyya; Fajar Rahayu; Nurfajriah Nurfajriah (P3M Politeknik Negeri Cilacap, 2020)
Urban farming (gardening in the middle of the city) is increasingly in demand by modern society. Urban farming provides business opportunities as well as being a lifestyle trend. One of the plants that can be cultivated at home is oyster mushroom. Oyster mushroom cultivation is quite easy but requires a special environment to grow up. To do mushroom cultivation at home, it is necessary to manage temperature and humidity to achieve optimal temperature and humidity. A temperature and humidity control system that can be monitored and controlled through the smartphoneis the result of the study. Temperature and humidity detected by the DHT22 sensor, then read by NodeMCU and sent to the Blynk application via a WiFi connection are considered as the input system. WiFi used by NodeMCU is the same as WiFi used by smartphones. Blynk on a smartphone will display the temperature and humidity read by NodeMCU. If the temperature and humidity are out of the optimal temperature and humidity range for oyster mushrooms, a notification will appear on the smartphone. Temperature and humidity control can be done by pressing the ON / OFF button on Blynk to turn on and turn off the lights or the fan as needed, so that the temperature and humidity return to optimal. Based on testing, the system successfully displays temperature and humidity on a smartphone, displays notifications and makes control. The relative error of the temperature measurement is 2.6% and the relative error of the humidity measurement is 3.2%.